(untitled) (Philological Studies, 2019)
This contribution focuses on the novel A Minuet for Guitar and its film adaptation with the title Farewell until the Next War. Firstly, the article deals with the novel from the perspective of modernist narrative devices and secondly, it focuses on the analysis of its film adaptation. Based on the anthropological-morphological method of film analysis it establishes that Živojin Pavlović used modernist narrative devices in film. Furthermore, it studies how, and with which film expressions and methods, stream of consciousness and memories are shown, as well as how essay style, fragmentariness and associational style are expressed in audio-visual representation.